Completing banking union - Thomas F. Huertas (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
To complete banking union, there should be a single European deposit insurance scheme (EDIS) alongside the single supervisor and the single resolution authority. This would ensure uniformity across the Eurozone and facilitate the removal of barriers to the mobility of liquidity and capital within the single market. That in turn would promote efficiency in the banking sector and in the economy at large - just at the time that the EU needs to boost growth in order to remain competitive with the US and China. The EDIS promise to promptly reimburse insured deposits at a failed bank in the Eurozone should be unconditional. But who will stand behind that commitment? Who is the "E" in EDIS? Is its promise credible, even in a crisis? If a deposit guarantee scheme fails to deliver what people expect, panic would very likely erupt. Instead of strengthening financial stability, deposit insurance could destroy it. Yet this is the risk that current proposals pose. They create the impression that there will be a single deposit guarantee scheme. There will not. Instead, there will be a complex set of liquidity and reinsurance arrangements among Member State schemes. These defects need to be remedied. To do so, we propose creating a European Deposit Insurance Corporation (EDIC) alongside national schemes. For banks that meet EDIC's strict entry criteria and decide to become members, EDIC will promise to reimburse promptly - in the event the member bank fails - 100 cents on the euro in euro for each euro of insured deposits, regardless of the Eurozone Member State in which the bank is headquartered. In effect, the single deposit guarantee scheme would be created via migration to EDIC rather than mutualisation of existing schemes. This would increase the mobility of capital and liquidity and lead to a convergence of interest rates across the Eurozone. That in turn will improve the effectiveness of monetary policy, foster integration and promote growth.
urn:nbn:de:hebis:30:3-512000
Keywords: 330